A New Model of Mixture Distribution Using a Survival Analysis of Cancer Patients - Sakthivel, M.; Pandiyan, P. (Brazilian Journal of Biometrics, 2025)
In this article, specific statistical considerations are typically required in order to select the best model for fitting cancer survival data. A new two-parameter distribution known as the Mixture of Lomax and Gamma Distribution (MLGD) is proposed in this article. Because of the unique way that the Gamma and Lomax distributions are mixed, this distribution is created as a special mixture of two distributions. Statistical properties, order statistics, entropy, and reliability analysis are also derived. The maximum likelihood estimation method can be used to estimate the parameters of the distribution. Lastly, a goodness-of-fit analysis is demonstrated on a set of data on cancer survival. It is compared to the fit and shows that the gamma and Lomax mixing distributions have more flexibility than the other distributions.